2018
DOI: 10.3390/biomedicines6040104
|View full text |Cite
|
Sign up to set email alerts
|

A New Role for Vitamin D: The Enhancement of Oncolytic Viral Therapy in Pancreatic Cancer

Abstract: Oncolytic viruses have emerged as a novel class of anti-cancer therapeutics with one virus already receiving United States Food and Drug Administration (FDA) approval (talimogene laherparepvec) and many others undergoing testing in clinical trials. These viruses have direct lytic effects on tumor cells as well as immunomodulatory functions to increase inflammatory cell infiltrates in the tumor microenvironment. Despite all of the advances in cancer care, pancreatic cancer remains a highly lethal malignancy. On… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 81 publications
(102 reference statements)
0
11
0
Order By: Relevance
“…Epidemiological studies show that vitamin D3 supplementation is effective in the improvement of vascular function [21,22] and has a beneficial effect on the function of the left ventricle in patients with heart failure [23,24,25]. In addition, vitamin D has been shown to inhibit the migration and growth of cancer cells [26,27,28,29]. However, it is unknown if calcitriol is also able to attenuate the progression of cancer cells apart from its beneficial effect in the inhibition of DoIC.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological studies show that vitamin D3 supplementation is effective in the improvement of vascular function [21,22] and has a beneficial effect on the function of the left ventricle in patients with heart failure [23,24,25]. In addition, vitamin D has been shown to inhibit the migration and growth of cancer cells [26,27,28,29]. However, it is unknown if calcitriol is also able to attenuate the progression of cancer cells apart from its beneficial effect in the inhibition of DoIC.…”
Section: Introductionmentioning
confidence: 99%
“…A pilot study of neoadjuvant paricalcitol in patients with resectable PDAC found 10-100 fold increased T cell migration into tumors after 28 days of treatment ( 193 ). Furthermore, a number of reviews suggest utilization of VDAs to inhibit immune-suppressive activity of stromal cells and the hope is that this will improve response to checkpoint inhibitors in patients with PDAC ( 194 , 195 ).…”
Section: Hypercalcemic Effect Of Vdr Ligandsmentioning
confidence: 99%
“…The density and impenetrability of the PDAC tumor microenvironment limit access to and prevent robust exposure of OVs to the proliferating PDAC cells. To overcome the specific challenges associated with the density of the PDAC microenvironment, the use of Vitamin D in conjunction with therapeutic agents or the use of hyaluronidase is currently being investigated for the potential to increase OV exposure to the tumor microenvironment and facilitate enhanced therapeutic efficacy [ 31 , 45 ]. One can also predict the challenges posed to other common strategies of immune system modulation through viral-induced transfection being limited due to PDAC microenvironment immunosuppression and lack of neoantigen expression.…”
Section: Introduction To Oncolytic Virusesmentioning
confidence: 99%